The Development of Tahfiz Integrated Module System - Hassanudin, Hana Mumtaz; Mohd Zin, Nur Ariffin (Applied Information Technology And Computer Science, 2026)
The Tahfiz Integrated Module System was developed to enhance task management and educational monitoring efficiency within Tahfiz institutions, specifically SMKA Putrajaya, under the TMUA program. The current manual system at TMUA suffers from fragmented data storage, a lack of centralized tracking, and minimal communication support between stakeholders, which negatively impacts performance assessment and data integrity. To address these issues, the system was built using a structured Waterfall methodology. The front end of the application was developed using Flutter and Dart within Android Studio, providing a mobile interface tailored for Android devices. For the backend, MySQL database integration was handled through SQLite, supporting centralized and secure data handling. Key modules include personnel registration and login, task and exercise management, analysis reporting, and extracurricular scheduling, all governed by role-based access for admins, teachers, and students. The system was evaluated through alpha and beta testing phases, with 92% User Acceptance Test (UAT) satisfaction indicating that the system effectively meets user expectations. Aligned with Malaysia's Digital Education Policy, the system contributes to digital transformation in Quranic education and improves institutional task administration, data centralization, and teaching outcomes.